Randomized Pilot Trial for a Community-Based Group Stretching Exercise Program for Chronic Low Back Pain - Marc Brodsky MD; Ann Hansen DVM, MD; Wendy Bjerke PhD (SAGE Publishing, 2019)
Background Authors of meta-analyses concluded that exercise therapy appears to be slightly effective at decreasing pain and improving function in adults with chronic low back pain (CLBP), particularly in health-care populations. Similar to health-care settings, community organizations provide wellness and lifestyle modification programs. Different versions of the Young Men's Christian Association (YMCA) Y's Way to a Healthy Back program were offered from 1974 to 2004. Champions of the YMCA program and authors of the pilot study designed a Healthy Back Curriculum to update and reintroduce the program. Objective: The research aim of this randomized pilot trial was to investigate the feasibility of a follow-up larger randomized controlled trial on the program's effectiveness for CLBP. The randomized pilot trial addressed subject recruitment, retention, and subject compliance with protocol. Methods: The pilot trial employed a 2-arm parallel group randomized design. Seventy-eight subjects aged 18 to 64 years with low back pain on at least half the days over the previous 6 months were assigned to either (1) a group stretching exercise arm with 12 weekly classes or (2) a self-care book arm. Results: Sixty participants, 30 in each group, completed the study. Out of the 130 members who accepted invitation, 60% were eligible. Retention rate over the 24-week study in the group stretching exercise arm was 30 out of 43 participants (70%). Participants in the group stretching exercise program attended an average of 5 of the 12 classes (42%). Participants completed baseline and follow-up self-report items with no missing data. Conclusion: The pilot study did not prove to be feasible based on the prespecified benchmarks. We suggest that a larger trial should include changes gleaned from the pilot study.